ON IMPORT SUBSTITUTION OF THE MEAT INDUSTRY FOR PROVIDING FUNCTIONS OF SOCIAL PROTECTION OF POPULATION: FEATURES AND ANALYSIS - Nassyrova, A.; Rudyk, N.; Shchegoleva, E.; Kolesnikova, E.; Viliguta, O.; Niyazbekova, Sh.; Abdul Kayum Jallal, Mir (Scientific Journal of Pedagogy and Economics, 2020)
The idea of import substitution, as well as its attendant problems and challenges, arise permanently and becomes relevant for national economies within the framework of national security concepts and socio-economic development strategies of different countries. Russia is no exception and ensuring social protection of the population is paramount for the sustainability of the interaction of social institutions and ensuring food and economic security in general at the regional and country levels. The meat and meat products market, being the largest segment of the domestic food market, has a significant impact on the country's food supply. The presented study discribes the features of domestic meat industry development in implementation of import substitution programs. Solving the problems of import substitution is not an instant procedure[3]. This is a set of long-term measures, in the implementation of which state bodies at all levels, business itself, and local governments should take part. The purpose of the work is to show the problems that the industry is facing at the present stage, the directions of their solutions and the tasks of the state in this mechanism. The current state of the industry, the volume of its financial support have been analyzed in the study. The state support of import substitution in the industry and its results are examined in detail. Based on data on the current state, the main problems of the development of the industry have been identified, the dynamics of import substitution in it has been shown, there have been formulated recommendations for the effective development of the industry in the long term.